A neural decision signal during internal sampling from working memory in humans - Van Ede, F; Nobre, A (Society for Neuroscience, 2024)
How humans transform sensory information into decisions that steer purposeful behaviour is a central question in psychology and neuroscience that is traditionally investigated during the sampling of external, environmental signals. The decision-making framework of gradual information sampling toward a decision has also been proposed to apply when sampling internal sensory evidence from working memory. However, neural evidence for this proposal remains scarce. Here we show (using scalp-EEG in male and female human volunteers) that sampling internal visual representations from working memory elicits a scalp-EEG potential associated with gradual evidence accumulation – the Central Parietal Positivity (CPP). Consistent with an evolving decision process, we show how this signal (i) scales with the time participants require to reach a decision about the cued memory content and (ii) is amplified when having to decide among multiple contents in working memory. These results bring the electrophysiology of decision making into the domain of working memory and suggest that variability in memory-guided behaviour may be driven (at least in part) by variations in the sampling of our inner mental contents.